Impact of Crossing Golden Sabahia and White Leghorn Chickens on Performance Traits: An Analysis of Heterosis, Additive Effects, and Performance Curves (Acta Scientiarum. Animal Sciences, 2026)
The current study was conducted to investigate the effect of crossbreeding between Golden Sabahia (GS) and White Leghorn (WL) strains on body weight (BW) and egg production traits and estimate crossbreeding parameters such as direct heterosis, additive effect and evaluating the growth and egg production curves. GS pure line had the significantly highest BW0, BW56, BW70 and BW84, however, it had a significantly lower BW14 than the crossbreds. Furthermore, the GS - sired crossbred was significantly heavier in BW14, BW28 and BW42 than the pure lines and the reciprocal cross. GS Ã— WL cross showed significantly higher daily body weight gains than the reciprocal cross except for BWG8 - 12. WL purebred line had the lowest EW90 among the strain groups, meanwhile, EW10 was at its highest mean in the GS Ã— WL crossbred. Moreover, WL Ã— GS crossbred had the lowest performance among the groups in terms of P10. Positive direct additive effects were shown for body weights and most egg production traits, indicating GS’s superior genetic potential. The direct additive effects were positive for the egg production traits studied apart from P10. Overall, the GS - sired crossbreds displayed the best performance in terms of growth rate and egg production, making them a promising option for poultry breeding programs.